2021
DOI: 10.1093/jac/dkab124
|View full text |Cite
|
Sign up to set email alerts
|

Thiocillin and micrococcin exploit the ferrioxamine receptor of Pseudomonas aeruginosa for uptake

Abstract: Background Thiopeptides are a class of antibiotics that are active against Gram-positive bacteria and inhibit translation. They were considered inactive against Gram-negative bacteria due to their inability to cross the outer membrane. However, we discovered previously that a member of this class, thiostrepton (TS), has activity against Pseudomonas aeruginosa and Acinetobacter baumannii under iron-limiting conditions. TS hijacks the pyoverdine siderophore receptors of P. aeruginosa to cross t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 80 publications
0
35
0
Order By: Relevance
“…In contrast, there was no antimicrobial activity in extracts from A. baumannii after association, indicating that MP1‐loaded MVs cannot deliver MP1 to that Gram‐negative bacterium, most likely due to the presence of the outer membrane. This is noteworthy, as pure MP1 also lacks activity toward Gram‐negative bacteria, which is believed to be due to the inability of MP1 to pass the outer membrane, except when specific receptors are present (Chan & Burrows, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, there was no antimicrobial activity in extracts from A. baumannii after association, indicating that MP1‐loaded MVs cannot deliver MP1 to that Gram‐negative bacterium, most likely due to the presence of the outer membrane. This is noteworthy, as pure MP1 also lacks activity toward Gram‐negative bacteria, which is believed to be due to the inability of MP1 to pass the outer membrane, except when specific receptors are present (Chan & Burrows, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thiocillin (38) ( Figure 10 ), produced by B. cereus ATCC 14579, has been previously reported to only target gram-positive bacteria but has recently been shown to also target gram-negative bacteria [ 112 ]. Its mechanism on gram-positive bacteria works by targeting the 50S ribosome and inhibiting its role in protein synthesis [ 113 ].…”
Section: Antimicrobial Metabolites and Their Mechanism Of Actionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 20, 2022. ; https://doi.org/10.1101/2022.09.20.508722 doi: bioRxiv preprint Previously we showed that the large thiopeptide antibiotics thiostrepton (TS) and thiocillin (TC) use TBDTs to enter P. aeruginosa to access their cytoplasmic target, the ribosome. TS exploits the pyoverdine transporters, FpvA and FpvB, while thiocillin uses the ferrioxamine transporter, FoxA (Figure 1) (Chan et al, 2020;Chan and Burrows, 2021;Ranieri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Together with the inner membrane proteins ExbB-ExbD, TonB harnesses the proton motive force to actively transport ligands through the transporters via a mechanism that remains incompletely understood (Klebba et al, 2021; Noinaj et al, 2010). Although TonB-dependent transporters (TBDTs) are considered ligand-specific, they can be exploited by antimicrobial compounds, bacteriophages, and bacteriocins for uptake, making them of interest for drug delivery across the outer membrane of Gram negatives (Chan and Burrows, 2021; Ferguson et al, 2000; Luna et al, 2020; Luscher et al, 2018; Mathavan et al, 2014; Rabsch et al, 2007; Ranieri et al, 2019; Salomon and Farias, 1993; White et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation